The European Union and China: The Need for a More Politicised Relationship. Issue 3 (9th September 2016) - Brown, Kerry; Beatson, Sam
Abstract: China and the European Union (EU) in 2016 have one of the largest economic relationships to the world, with a network of strategic dialogues covering areas from environment to agriculture. Despite this, their relationship is a hard one to encapsulate. President Xi Jinping's idea of a 'civilisational' partnership seem abstract, but at least opens up the possibility of the EU conceptualizing its relationship with China as not solely transactional, but something more political. This paper argues that conferring Market Economy Status on China will be a key issue in marking this transition between the EU seeing its link with China solely in economic terms, and looking for a stronger political dimension. The conclusion is that both sides can no longer pretend they are simply trade blocks interacting with each other.